Serum Lactate, Brain Magnetic Resonance Imaging and Outcome of Neonatal Hypoxic Ischemic Encephalopathy after Therapeutic Hypothermia - Ming-Chou Chiang; Reyin Lien; Shih-Ming Chu; Peng-Hong Yang; Jainn-Jim Lin; Jen-Fu Hsu; Ren-Huei Fu; Kuang-Lin Lin (Elsevier, 2016)
Serum lactate was used to predict the severity and outcome of neonatal hypoxic ischemic encephalopathy (HIE) before the era of therapeutic hypothermia (TH). There is no report on neurodevelopment (ND) outcome of neonates with HIE treated with TH in Taiwan. Methods: Between April 2011 and December 2012, newborn infants admitted to Chang Gung Memorial Hospital (CGMH), with gestational age > 35 weeks and birth weight ≥ 1800 g, who had acute perinatal events, evidence of significant fetal compromise, and ongoing clinical encephalopathy were prospectively enrolled for TH. Whole body cooling method was used to maintain the affected neonate's esophageal temperature at 33.5 ± 0.5°C for 72 hours. Demographic data were recorded and hemogram, biochemical parameters, serum lactate, and creatine kinase (CK) were measured as well. Brain magnetic resonance imaging (MRI) was performed between 7 and 14 days of life. ND outcome of infants was evaluated by Bayley Scales of Infant Development, third edition (BSID-III) at 24 months of corrected age. Poor ND (PND) outcome was defined as infants surviving with either disability or ND delay. Results: Seventeen patients were enrolled. Fifty-nine percent of babies (10/17) were born through cesarean section and 77% of babies (13/17) were transferred from outside hospitals. Six babies were moderate HIE and 11 babies were severe HIE. Among the 14 surviving patients, eight infants had PND outcome. There was no difference in demographic data between infants with and without PND. Serum level of lactate (mg/dL) after 72 hours of TH was higher (35.6 vs. 13.8, p = 0.042) in infants with PND. Neonates with abnormal brain MRI findings were also associated with PND (p = 0.01). Conclusion: This is the first report on ND outcome of neonates with HIE treated with TH in Taiwan. Higher serum level of lactate following TH and abnormal results of brain MRI are associated with poor ND outcome.